Pay schemes, bargaining, and competition for talent - Assar Lindbeck; Jörgen W. Weibull (Research Institute of Industrial Economics (IFN), 2015)
The paper provides a framework for analysis of remuneration to agents whose task is to make well-informed decisions on behalf of a principal, with managers in large corporations as the most prominent example. The principal and agent initially bargain over the pay scheme to the latter. The bargaining outcome depends both on competition for agents and on the relative bargaining power of the two parties, given their outside options, thus allowing for the possibility that the agent may be the current CEO who may have considerable power. Having signed a contract, the agent chooses how much effort to make to acquire information about the project at hand. This information is private and the agent uses it in his subsequent decision whether or not to invest in a given project. In model A the agent's effort to acquire information is exogenous, whereas in model E it is endogenous. Model A lends no support for other payment schemes than flat salaries is weak. Model E contains a double moral hazard problem; how much information to acquire and what investment decision to make. As a consequence, the equilibrium contracts in model E involve both bonuses and penalties. We identify lower and upper bounds on these, and study how the bonus and bonus rate depend on competition and bargaining power. We also analyze the nature of contracts when the agent is overconfident.
Keywords: D01; D82; D86; G11; G23; G30; 330; Principal-agent; Investment; Endogenous uncertainty; Contract; Bonus; Penalty